Greek Texts and Armenian Traditions. (Trends in classics. Supplementary volumes ;, 2016)
This volume explores, with an interdisciplinary approach, the interaction between the ancient Armenian and Greek worlds and their literatures, focusing on the Armenian translations of Greek texts, the historical context and historiographic sources, the Armenian reception of biblical, Christian and Byzantine literature, as well as philological, linguistic and lexical aspects.